Facilitators and barriers to using smart TV among older adults in care settings: a scoping review protocol - Lillian Hung; Mario Gregorio; Karen Lok Yi Wong (BMJ Open)
Introduction The objective of the scoping review is to understand what has been reported in the literature regarding facilitators and barriers to using smart television (smart TV) among older adults in care settings.Methods and analysis The scoping review will adopt the Joanna Briggs Institute scoping review methodology. It will occur between March and August 2022. It will consider literature on using smart TV with older adults in care settings. A three-step search strategy will be applied: (1) to identify keywords and index terms from MEDLINE and CINAHL; (2) to do a search using identified keywords and index terms across chosen databases (MEDLINE, CINAHL, Embase, Web of Science, Scopus, AgeLine, PsycINFO, Web of Science, ProQuest and Google) and (3) to hand search the reference lists of all selected literature for additional literature. Further, we will search using Google for grey literature. Two research assistants will independently screen the titles and abstracts by referring to the inclusion criteria. After that, two researchers will independently assess the full text of selected literature by referring to the inclusion criteria. We will present the data in a table with narratives that answer the questions of the scoping review.Ethics and dissemination The scoping review does not require ethics approval because it collects data from the publicly available literature. The findings will offer insights to inform the use of smart TV among older adults in care settings for education, practice, policy and future research. The scoping review results will also be disseminated through conference presentations and an open-access publication in a peer-reviewed journal.